Graph-Based Modelling in Engineering - Zawiślak, Stanisław; Rysiński, Jacek; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents versatile, modern and creative applications of graph theory in mechanical engineering, robotics and computer networks. Topics related to mechanical engineering include e.g. machine and mechanism science, mechatronics, robotics, gearing and transmissions, design theory and production processes. The graphs treated are simple graphs, weighted and mixed graphs, bond graphs, Petri nets, logical trees etc. The authors represent several countries in Europe and America, and their contributions show how different, elegant, useful and fruitful the utilization of graphs in modelling of engineering systems can be. .
Preface -- Part I Basics and theoretical aspects of graph and network modelling -- Why Bond Graphs in Model Construction, by R. Ibănescu -- Structural Importance and Local Importance in Network Reliability, by P. Tittmann, S. Kischnick -- Access Distribution Scheme To The Computer System Based On Fuzzy Logic, by A. Shaikhanova, A. Zolotov, L. Dubchak, M. Karpinski, V. Karpinskyi -- Problem of Medicines Distribution on the Example of Pharmaceutical Wholesale, by M. Cieśla, B. Mrówczyńska -- Part II Modelling of mechanical systems -- Bond Graph Model of Robot Leg, by B. Gola, J. Kopeć, J. Rysiński, S. Zawiślak -- Kinematical Analysis of Variants of Wind Turbine Drive by Means of Graphs, by J. Drewniak, J. Kopeć, S. Zawiślak -- Graph-Based Algorithm for the Evaluation of the Mechanical Efficiency of Epicyclic Gear Drive in Hybrid Scooters, by P. Coaccioli, E.Pennestrì -- Graph-theoretic modelling and sensitivity analysis of dynamic systems, by J. Banerjee, J. McPhee -- Three-Dimensional Analysis of Vehicle Stability Using Graph Theory, by G. Moreno, R.L.P. Barreto, R.S. Vieira, L. Nicolazzi, D. Martins -- Part III Modeling of production processes -- Petri Nets for Computer Aided Group Technology, by R. Stryczek -- Graph theory in product development planning, by I. Kutschenreiter-Praszkiewicz -- A digital pattern approach to 3D CAD modelling of automotive car door assembly by using directed graphs, by S. Patalano, F. Vitolo, A. Lanzotti -- Part IV Graph-based aid and modelling of design tasks -- Application of game graphs to describe the inverse problem in the designing of mechatronic vibrating systems, by A. Deptuła -- Graphic matrix formalization of logical decision trees in the optimization of machine systems, by A. Deptuła, M.A. Partyka -- The Class of Objects Graph Model as Dataware of Structural Synthesis System, by O.V. Malina, E.G. Zarifullina -- Part V Miscellaneous -- Search Module as Tool for Improvement of Classifier, by E.G. Zarifullina, O.V. Malinaand I.M. Nekipetova -- Kazimierz Kuratowski - Biography and Genesis of the Theorem on Planar Graphs, by J. Wojnarowski, S. Zawiślak -- Author Index. .
Keywords: Engineering design; Mathematics; Mechanics, Applied; Control engineering; Robotics; Automation; Engineering Design; Applications of Mathematics; Engineering Mechanics; Control, Robotics, Automation